Análise das características elétricas e fluorescentes da matriz cerâmica ortoniobato de lantânio (LaNbO4) co-dopada com íons terras raras praseodímio e itérbio - Nascimento, João Paulo Costa do (2019)
In this work, new materials based on Pr3+ – Yb3+ co-doped LaNbO4 phosphors were prepared. The synthesis was performed by using the solid state reaction method where the dopant ions were inserted into the La3+ sites. The systems were analyzed through X-ray diffraction, fluorescence upconversion and electrical measurements in the radiofrequency (RF) region. According to the X-ray diffraction no secondary phase has been detected in the doped samples, and that the lattice parameters followed the Vegard's law. Impedance spectroscopy showed that the Pr/Yb doping caused significant changes in the dielectric properties of the LNO. This can be ascribed to the generation of defects in the crystalline structure of the materials which compensate the positive charge coming from the entry of Pr3+/ Pr4+ and Yb3+ ions. In fluorescence, the Pr-Yb doped materials exhibited emissions in the visible (RGB) and infrared regions referring to the electronic transitions between the 4f orbitals of the Pr3+ ion. The CIE color coordinates of the samples shift from the green region to the blue region with increasing the Yb3+ concentration due to the great increase of the tristimulus Z. It was also evaluated the behavior of the chromatic coordinates with the pumping power. Systems LPY2% and LPY8% did not show significant variations in the CIE characterizing these materials as non-tunable phosphors for use in optical devices in the security area.